HIV-1 Tropism Testing and Clinical Management of CCR5 Antagonists: Quebec Review and Recommendations. Issue 4 (2013) - Tremblay, Cécile; Hardy, Isabelle; Lalonde, Richard; Trottier, Benoit; Tsarevsky, Irina; Vézina, Louis-Philippe; Roger, Michel; Wainberg, Mark; Baril, Jean-Guy
Abstract : HIV-1 tropism assays play a crucial role in determining the response to CCR5 receptor antagonists. Initially, phenotypic tests were used, but limited access to these tests prompted the development of alternative strategies. Recently, genotyping tropism has been validated using a Canadian technology in clinical trials investigating the use of maraviroc in both experienced and treatment-naive patients. The present guidelines review the evidence supporting the use of genotypic assays and provide recommendations regarding tropism testing in daily clinical management.